2021
DOI: 10.1027/1016-9040/a000460
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on the Majority Population, Ethno-Racial Minorities, and Immigrants

Abstract: Abstract. The COVID-19 pandemic constitutes an unprecedented threat for individuals and societies, revealing stark inequalities in preparedness, exposure, and consequences. The present systematic literature review complements extant knowledge on disasters and pandemic diseases with programmatic research on the COVID-19 pandemic. Building upon an integrative definition of threat, we merge intra-personal threat regulation with group dynamics and inter-group relations. Via streamlined methods of knowledge synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 86 publications
1
12
0
1
Order By: Relevance
“…By defining threat as the psychological appraisal of external or internal stressors, Politi et al (2021) argued that the COVID-19 outbreak threatened several spheres of people’s life, ranging from personal fears of getting the virus to collective concerns about society. We believed that the COVID-19 outbreak provoked an acute work stress increase too, because containment measures forced people to adjust to new working conditions (Rudolph et al, 2021), thereby threatening their professional life.…”
Section: Teachers’ Threat Appraisals and Emotional Exhaustionmentioning
confidence: 99%
“…By defining threat as the psychological appraisal of external or internal stressors, Politi et al (2021) argued that the COVID-19 outbreak threatened several spheres of people’s life, ranging from personal fears of getting the virus to collective concerns about society. We believed that the COVID-19 outbreak provoked an acute work stress increase too, because containment measures forced people to adjust to new working conditions (Rudolph et al, 2021), thereby threatening their professional life.…”
Section: Teachers’ Threat Appraisals and Emotional Exhaustionmentioning
confidence: 99%
“…Prolonged for weeks, and even for over 6 months (see Costabel, 2020 on the case of Argentina), these forms of containment have been associated with a deterioration in the population’s mental health, although not in all contexts, and with strong disparities between social groups by age, gender, and socio-economic status. In particular, it has been reported that some critical features increase in the most vulnerable groups, for example, those with pre-existing mental health conditions, as well as in women, the economically under-privileged and the youngest (Bellotti et al, 2021; Daly et al, 2020; Kuhn et al, 2021; Mohler-Kuo et al, 2021; Politi et al, 2021; Singh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These imply that contextually induced conflicts commonly existed for Asian and Native American groups during the pandemic. Such conflicts would potentially increase hostility toward these two groups ( Nir et al, 2022 ) and reduce the financial and health aids they could receive from society during the pandemic ( Adler et al, 2022 ; Politi et al, 2021 ). Our findings thereby advocate for monitoring public opinion and sentiment online to better cope with the disparities in reality during the pandemic.…”
Section: Discussionmentioning
confidence: 99%